Embryonic development and perinatal skeleton in a limbless, viviparous lizard, Anguis fragilis (Squamata: Anguimorpha) - Tomasz Skawiński; Grzegorz Skórzewski; Bartosz Borczyk (PeerJ, 2021)
Despite the long history of embryological studies of squamates, many groups of this huge clade have received only limited attention. One such understudied group is the anguimorphs, a clade comprising morphologically and ecologically very diverse lizards. We describe several stages of embryonic development of Anguis fragilis, a limbless, viviparous anguimorph. Interestingly, in several clutches we observe high morphological variation in characters traditionally important in classifying embryos into developmental stages. The causes of this variation remain unknown but environmental factors do not seem to be very important. Additionally, we describe the state of ossification in several perinatal specimens of A. fragilis. The cranial skeleton is relatively poorly ossified around the time of birth, with all of the bones constituting the braincase unfused. On the other hand, the vertebral column is well ossified, with the neurocentral sutures closed and the neural arches fused in all postatlantal vertebrae. Such an advanced state of ossification may be related to the greater importance of the vertebral column in locomotion in limbless species than in ones with fully-developed limbs. Numerous factors seem to affect the state of ossification at the time of hatching or birth in squamates, including phylogenetic position, mode of reproduction and, potentially, limblessness. However, data from a greater number of species are needed to reach firmer conclusions about the relative importance of these variables in certain clades.